Effect of preperformance routine on advanced swimmers` performance and motor efficiency, self-efficacy, and idiosyncratic emotions - Richard, V.; Mason, J.; Alvarez-Alvarado, S.; Perry, I.; Lussier, B.; Tenenbaum, G. (The Sport Psychologist, 2021)
The aim of the present study was to compare the effectiveness of a learned preperformance routine (PPR) with an intuitively developed one before a simulation race on advanced swimmers` speed and motor efficiency, as well as self-efficacy and emotional regulation. In total, 46 National Collegiate Athletic Association Division I swimmers were stratified to either the control (intuitively developed PPR) or the PPR condition, which included four instructional sessions aimed at developing a PPR. A simulated competitive race was organized before and after the intervention. For each simulation, speed and motor efficiency were measured during the race, and self-efficacy and emotions, after the completion of the race. Nonsignificant effects were revealed for speed, motor efficiency, and self-efficacy following the intervention. However, performing a learned PPR prior to racing significantly influenced the swimmers` emotional state. These results provide some support for the effect of a PPR on emotional regulation prior to a swimming race.